Internalizing Religious Moderation Values through Project-Based Learning in English Language Teaching: A Literature Review - Arini Yusti; Sulistiyarini Ika (2022)
Some reports have uncovered that many religious intolerance and violation cases still appeared in Indonesia recently. As a consequence, internalizing the values ​​of religious moderation to higher education students is urgently needed. To realize this crucial demand, integrating those values into the learning materials in ELT (English Language Teaching) can be started from the subject concerning teaching media for young learners which learns about making effective and fun learning media for teaching children English. Mostly the materials are still focused on learning English only; no topic is specifically related to inculcating religious moderation on making the teaching media that must be mastered by the students as teacher candidates. This paper tries to explain the concepts of making English teaching media for young learners carried out through Project-Based Learning (PjBL) which allows students to work collaboratively to produce some works or products that are relevant to real life, problem-solving, and communicative. Therefore, the products can be used to teach English to children which include the values ​​of religious moderation. This research is a literature review. The results show that the values ​​of religious moderation that can be internalized into lecture materials as well as teaching media are justice, balance, tolerance, and equality. Those values can be embedded through stories, examples, pictures, questions, or even games in teaching media. The research results can be a reference to develop learning materials in ELT and to conduct similar further research.